2012
DOI: 10.1136/bmj.e4757
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma attributable to sunbed use: systematic review and meta-analysis

Abstract: Objective To estimate the burden of melanoma resulting from sunbed use in western Europe.Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
532
9
19

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(568 citation statements)
references
References 78 publications
8
532
9
19
Order By: Relevance
“…14,15 Two recent studies provide estimates of the number of skin cancers that may be caused by indoor tanning each year; more than 170,000 cases of squamous and basal cell carcinomas of the skin may be due to indoor tanning in the U.S. annually, and more than 3400 cases of melanoma may be due to indoor tanning in Europe. 16,17 Melanoma causes more deaths than any other skin cancer, and its incidence is increasing, particularly among non-Hispanic whites and women; increases have also been noted among all tumor thicknesses. 18 Additionally, melanoma is one of the most commonly diagnosed cancers among adolescents and young adults in the U.S. 19,20 Indoor tanning before age 35 years increases the risk of melanoma by 60%-80% or more, possibly because of longer duration of use.…”
Section: Indoor Tanning and Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Two recent studies provide estimates of the number of skin cancers that may be caused by indoor tanning each year; more than 170,000 cases of squamous and basal cell carcinomas of the skin may be due to indoor tanning in the U.S. annually, and more than 3400 cases of melanoma may be due to indoor tanning in Europe. 16,17 Melanoma causes more deaths than any other skin cancer, and its incidence is increasing, particularly among non-Hispanic whites and women; increases have also been noted among all tumor thicknesses. 18 Additionally, melanoma is one of the most commonly diagnosed cancers among adolescents and young adults in the U.S. 19,20 Indoor tanning before age 35 years increases the risk of melanoma by 60%-80% or more, possibly because of longer duration of use.…”
Section: Indoor Tanning and Cancer Riskmentioning
confidence: 99%
“…18 Additionally, melanoma is one of the most commonly diagnosed cancers among adolescents and young adults in the U.S. 19,20 Indoor tanning before age 35 years increases the risk of melanoma by 60%-80% or more, possibly because of longer duration of use. 3,13,16,21 In addition to the morbidity and mortality it causes, skin cancer poses a substantial economic burden in the U.S. 22,23 The treatment of melanoma and nonmelanoma skin cancer costs an estimated $1.7 billion each year. Costs due to lost productivity are estimated to be $3.8 billion.…”
Section: Indoor Tanning and Cancer Riskmentioning
confidence: 99%
“…Meta-analyses indicate that any lifetime indoor tanning increases the risks of non-melanoma skin cancer by 29-67 % and melanoma by approximately 20 %, and these risks are increased with greater indoor tanning exposure [3,4]. Despite modest declines in the prevalence of indoor tanning in the USA recently, indoor tanning remains prevalent among nonHispanic white women 18 to 30 years of age [5].…”
Section: Introductionmentioning
confidence: 99%
“…Health belief model, Indoor tanning, Tanning cessation, Tanning quitting, Qualitative research Indoor tanning is a strong risk factor for melanoma [2]. In 2009, the World Health Organization's International Agency for Research on Cancer Working Group (IARC) classified ultraviolet (UV)-emitting tanning devices (tanning beds, lamps, and booths) as carcinogenic to humans [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, the World Health Organization's International Agency for Research on Cancer Working Group (IARC) classified ultraviolet (UV)-emitting tanning devices (tanning beds, lamps, and booths) as carcinogenic to humans [3]. Results from recent meta-analysis that included 27 observational studies published within the past 30 years, showed that the risk of cutaneous melanoma was increased by 20 % for ever users of indoor tanning devices with artificial ultraviolet light, and the risk of melanoma was doubled when use started before the age of 35 years [2]. Besides melanoma, indoor tanners are at high risk for nonmelanoma skin cancers (squamous cell carcinoma, basal cell carcinoma) [4], premature aging including loss of skin firmness, solar elastosis, and wrinkles [5, 6], skin burns [7], and eye damage [8,9].…”
mentioning
confidence: 99%